The Chimeric Self: A Neo Naturalist Bundle Theory of the Self - Compiani, Lucrezia (Frontiers in Psychology, 2019)
In the contemporary cognitive science and philosophy of mind debate the definition of the ontology of the Self is difficult if not downright dubious. Thus, different theories aim to provide an account, especially where further neuroscientific research could be implemented. To this extent, the identity of the Self is suggested to be pinpointed by virtue of its specific set of mechanical features or brain functions, or it is considered the product of cognitive and conceptual capacities that build representations and narratives about ourselves. In this paper, I propose an alternative approach, based on the Spread Mind Theory (Manzotti, 2017a). Starting from the idea that the Self isn’t just an aprioristic or transcendental form, I claim, endorsing a Neo Naturalist approach, that our first-personal experience is identical to the external objects which, due to a physical relation, constitute the same experience. Thanks to an externalist explanation of the experience of the Self it is possible to avoid multiple ontologies, causal foundationalism, naïve materialism and questions begging about what we should explain. Clarifying the concept of the Self, as a bundle of relative objects which are identical with the experiences themselves, allows us to draw a physical ontology, based on the neutral (and natural) idea of relative existence rather than any posited concept of subjectivity.